Arm motor control as predictor for hypertonia after stroke: A prospective cohort study - De Jong, Lex; Hoonhorst, M.; Stuive, I.; Dijkstra, P. (W.B. Saunders Co., 2011)
Objectives: To analyze the development of hypertonia in the hemiparetic elbow flexors, and to explore the predictive value of arm motor control on hypertonia in a cohort of first-ever stroke survivors in the first 6 months poststroke. Design: A prospective cohort study. Setting: A cohort of stroke survivors from a large, university-affilliated hospital in The Netherlands. Participants: Patients (N=50) with first-time ischemic strokes and initial arm paralysis who were admitted to a stroke unit. Interventions: Not applicable. Main Outcome Measures: At 48 hours, 10 to 12 days, 3 and 6 months poststroke, hypertonia and arm motor control were assessed using the Modified Ashworth Scale and the Fugl-Meyer Assessment arm score. Results: The incidence rate of hypertonia reached its maximum before the third month poststroke (30%). Prevalence was 42% at 3 and 6 months. Participants with poor arm motor control at 48 hours poststroke were 13 times more likely to develop hypertonia in the first 6 months poststroke than those with moderate to good arm motor control. These results were not confounded by the amount of arm function training received. Conclusions: Hypertonia develops in a large proportion of patients with stroke, predominantly within the first 3 months poststroke. Poor arm motor control is a risk factor for the development of hypertonia. © 2011 American Congress of Rehabilitation Medicine.